Fingolimod Augments Monomethylfumarate Killing of GBM Cells - Dent, Paul; Booth, Laurence; Roberts, Jane L.; Poklepovic, Andrew; Hancock, John F. (Frontiers in Oncology, 2020)
Previously we demonstrated that the multiple sclerosis drug dimethyl fumarate (DMF) and its plasma breakdown product MMF could interact with chemotherapeutic agents to kill both GBM cells and activated microglia. The trial NCT02337426 demonstrated the safety of DMF in newly diagnosed GBM patients when combined with the standard of care Stupp protocol. We hypothesized that another multiple sclerosis drug, fingolimod (FTY720) would synergize with MMF to kill GBM cells. MMF and fingolimod interacted in a greater than additive fashion to kill PDX GBM isolates. MMF and fingolimod radiosensitized glioma cells and enhanced the lethality of temozolomide. Exposure to [MMF + fingolimod] activated an ATM-dependent toxic autophagy pathway, enhanced protective endoplasmic reticulum stress signaling, and inactivated protective PI3K, STAT and YAP function. The drug combination reduced the expression of protective c-FLIP-s, MCL-1, BCL-XL and in parallel caused cell-surface clustering of the death receptor CD95. Knock down of CD95 or over-expression of c-FLIP-s or BCL-XL suppressed killing. Fingolimod and MMF interacted in a greater than additive fashion to rapidly enhance reactive oxygen species production and over-expression of either thioredoxin or super-oxide dismutase 2 significantly reduced the drug-induced phosphorylation of ATM, autophagosome formation and [MMF + fingolimod] lethality. In contrast, the production of ROS was only marginally reduced in cells lacking ATM, CD95, or Beclin1. Collectively, our data demonstrate that the primary generation of ROS by [MMF + fingolimod] plays a key role, via the induction of toxic autophagy and death receptor signaling, in the killing of GBM cells.